Pengaruh Rangkaian Abjad Warna Terhadap Peningkatan Daya Baca Siswa-Siswi Kelas 1 MI Miftahul Ulum (International Forum of Researchers and Lecturers, 2024)
The influence of a color alphabet learning media to provide an understanding of memorizing an alphabet to improve the reading power of class 1 MI Miftahul Ulum students, where in this learning students are provided with a color alphabet teaching aid to make it easier for students to memorize the alphabet and improve their reading ability. In this study, the researcher formulated a problem whether color alphabet learning media would affect the reading ability of grade 1 students at MI Miftahul Ulum. In this research, the